Trends and Developments in Chinese Insolvency Law: The First Decade of the PRC Enterprise Bankruptcy Law. (25th October 2018) - Steele, Stacey; Godwin, Andrew; Chun, Jin; Changyin, Han; Yimin, Ren; Weihong, Chi
Abstract: Insolvency law in the People's Republic of China (PRC) has gained increased prominence in the last five years in light of changing economic circumstances and government policies. This Article analyzes trends and developments in Chinese insolvency law since the enactment of the PRC Enterprise Bankruptcy Law in 2007, focusing on the dynamic transformation of insolvency practice, jurisprudence, and the profession over the last five years. It also draws on examples from Japan to highlight that China is not alone in relation to a number of contemporary debates and developments in insolvency law. Moreover, the Article brings together academic, judicial, and practitioner perspectives to examine key contemporary issues in China, including the influence of Chinese courts; the treatment of secured creditors; the professionalization, appointment, and remuneration of insolvency practitioners; and reorganizations of listed companies, unlisted real estate companies, and unlisted foreign investment enterprises. The Article also emphasizes the different rates of development in more sophisticated economic regions, such as Shenzhen City and Zhejiang Province, from which recent data and case studies are drawn. Finally, the Article analyzes China's approach to cross-border insolvencies. Whilst challenges remain, the Article evidences China's indigenous and increasingly sophisticated insolvency framework and highlights future innovations including publication of insolvency-related information and the potential for a personal insolvency regime.